PENINGKATAN KEMAMPUAN PENGAWAS KEUANGAN DI DESA MOODU KECAMATAN KOTA TIMUR - William Indra S Mooduto; Adinda Lestari; Farlin Musa (LPPM Universitas Bina Mandiri Gorontalo, 2024)
Village financial management is an important aspect in village development. However, the lack of financial supervisor capacity is often an obstacle in achieving good governance. This community service activity aims to improve the capacity of financial supervisors in Moodu Village, East Kota District. The methods used include training, mentoring, and ability evaluation. The results show a significant increase in understanding and skills in village financial management. This activity is expected to be a model for other villages in improving financial accountability.